Adsorption of Cobalt (II) on Layered Double Hydroxides (Mg/Al and Ca/Al) In Aqueous Medium : Kinetic and Thermodynamic Aspect - Neza Rahayu Palapa; Tarmizi Taher; Muhammad Said; Risfidian Mohadi; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Layered double hydroxides Mg/Al and Ca/Al has been synthesized by co-precipitation method with molar ratio M2+:M3+ (3:1) at pH 10. The synthesized materials were characterized by XRD and FTIR. The materials were used as adsorbent for the removal Cobalt (II) in aqueous solution. The adsorption experiments were studied through some variables adsorption such as variation of contact time, variation of temperature and variation of initial concentration. Kinetic parameters was obtained from variation of contact time. Data was analyzed by pseudo-first-order and pseudo-second-order kinetics models in linear analyses. The kinetic studies showed that the adsorption process more fitted by pseudo-second-order than pseudo-first-order based on coefficient correlation. Isotherm parameters was calculated using Langmuir and Freundlich isotherm models. The adsorption process was spontaneous and endothermic.